Interpretasi Struktur Bawah Tanah pada Sistem Sungai Bribin dengan Metode Geo - Khafidh Nur Aziz; Yosaphat Sumardi; Denny Darmawan; Nugroho Budi Wibowo (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
This research was aimed to determine the distribution pattern of magnetic field anomaly and to identify the lithology of underground structure in Bribin Karst using geomagnetic method. Research location was Semanu Sub-district, Gunungkidul Regency at UTM coordinate of 464061 mT-464929 mT and 9111097 mU-9111970 mU. The data were taken using G-5 Proton Precession Magnetometer (PPM) by looping method. The result showed that the distribution pattern of the magnetic field anomaly in Karst Bribin has value of 330 nT - 530 nT and anomaly values reflecting the system of Bribin River has value of 400 nT-460 nT. The lithology of underground structure in Karst Bribin has susceptibility value of -0.069 (in SI) - 0.0661 (in SI) with depth 200 m associated with limestone, tuff, gypsum, rock salt, and minerals calcite and anhydrite and the lithology associated with the system of Bribin River has susceptibility value -0.069 (in SI) associated with gypsum, rock salt, and minerals anhydrite.